Bioaccumulation and toxicity of selenium compounds in the green alga Scenedesmus quadricauda - Umysová, Dása; Vítová, Milada; Dousková, Irena; Bisová, Katerina; Hlavová, Monika; Cízková, Mária; Machát, Jirí; Doucha, Jirí; Zachleder, Vilém (BMC plant biology, 2009)
BACKGROUND: Selenium is a trace element performing important biological functions in many organisms including humans. It usually affects organisms in a strictly dosage-dependent manner being essential at low and toxic at higher concentrations. The impact of selenium on mammalian and land plant cells has been quite extensively studied. Information about algal cells is rare despite of the fact that they could produce selenium enriched biomass for biotechnology purposes. RESULTS: We studied the impact of selenium compounds on the green chlorococcal alga Scenedesmus quadricauda. Both the dose and chemical forms of Se were critical factors in the cellular response. Se toxicity increased in cultures grown under sulfur deficient conditions. We selected three strains of Scenedesmus quadricauda specifically resistant to high concentrations of inorganic selenium added as selenite (Na2SeO3) - strain SeIV, selenate (Na2SeO4) - strain SeVI or both - strain SeIV+VI. The total amount of Se and selenomethionine in biomass increased with increasing concentration of Se in the culturing media. The selenomethionine made up 30-40% of the total Se in biomass. In both the wild type and Se-resistant strains, the activity of thioredoxin reductase, increased rapidly in the presence of the form of selenium for which the given algal strain was not resistant. CONCLUSION: The selenium effect on the green alga Scenedesmus quadricauda was not only dose dependent, but the chemical form of the element was also crucial. With sulfur deficiency, the selenium toxicity increases, indicating interference of Se with sulfur metabolism. The amount of selenium and SeMet in algal biomass was dependent on both the type of compound and its dose. The activity of thioredoxin reductase was affected by selenium treatment in dose-dependent and toxic-dependent manner. The findings implied that the increase in TR activity in algal cells was a stress response to selenium cytotoxicity. Our study provides a new insight into the impact of selenium on green algae, especially with regard to its toxicity and bioaccumulation.
Keywords: kyselina selenová; selenomethionin; Selenium Compounds; síra; Dose-Response Relationship, Drug; vztah mezi dávkou a účinkem léčiva; Thioredoxin-Disulfide Reductase; Scenedesmus; Biomass; sloučeniny selenu; Selenomethionine; Sodium Selenite; Sulfur; thioredoxin-disulfidreduktasa; seleničitan sodný; biomasa; Selenic Acid